TEACHING SPOKEN ENGLISH IN SPAIN: CLASSROOM PRACTICES AND TEACHERS´’ PERCEPTIONS - GARCÍA-SAMPEDRO, MARTA (Journal of Education Culture and Society, 2021)
Aim. This article presents the results obtained in a qualitative research related to classroom practices and perceptions of teachers of English as a foreign language in Spain. The aim of this study is to present examples of good teaching practices, including the types of resources, materials and assessment used in spoken English teaching. Methods. A qualitative investigation that used ethnographic (non-participant) observation in primary and secondary English classes was implemented in thirty-two schools. Additionally, twenty semi-structured interviews with primary and secondary teachers were conducted. Results and conclusion. The results show significant differences between both applied methods Non-participant observation indicates that spoken communication in English is not practised sufficiently. However, based on interview results, teachers do apply appropriate language learning strategies that could allow them to successfully teach speaking skills in their students. The results imply that in Spain, there are still many teachers and educational institutions that follow the Grammar Translation Method and other traditional methodologies, which still focus primarily on writing skills. However, several examples of good practices and inspiring methodological and motivational strategies have been found throughout this research, which might be considered as a precedent for those that focus on writing approaches. Cognitive value. This article displays an original research supported by University of Oviedo, through which, the reader can approach to the teaching of spoken English in Spain by means of some teachers´ perceptions and examples of good practices.